CONFLITOS URBANOS EM MEDELLÍN E SÃO PAULO: dispositivos de publicização e cursos de ação para o direito à cidade - Morgana G. Martins Krieger; Marlei Pozzebon (Revista de Políticas Públicas, 2022)
High urbanization rates and low capacity to serve citizens result in constant urban conflicts in Latin America. Urban evictions make up this scenario and, although also caused by public policies, they are understudied in this area. This paper addresses this gap by investigating how, in the course of an urban conflict, the various actors interact to change the urban transformation process. The paper presents an analytical framework combining the right to the city with the sociology of public problems, which is employed to appreciate two cases of evictions, in São Paulo and Medellín, prepared from extensive field research. The paper advances in two contributions: in the creation and operationalization of the framework for the analysis of urban conflicts and in the identification of the publicizing devices and courses of action that favor or impede the attainment of the right to the city.